Bài làm
\(\left(x-\frac{2}{3}\right)\times3=\frac{3}{4}\)
\(x-\frac{2}{3}=\frac{3}{4}\div3\)
\(x-\frac{2}{3}=\frac{3}{4}\times\frac{1}{3}\)
\(x-\frac{2}{3}=\frac{1}{4}\)
\(x=\frac{1}{4}+\frac{2}{3}\)
\(x=\frac{3}{12}+\frac{8}{12}\)
\(x=\frac{11}{12}\)
Vậy \(x=\frac{11}{12}\)
# Chúc các em học tốt #
(x-2/3)= 3/4:3
x-2/3 = 1/4
x=1/4+2/3
x=11/12
Nhớ k nhé
\(\left(x-\frac{2}{3}\right)\times3=\frac{3}{4}\)
\(x-\frac{2}{3}=\frac{3}{4}\times\frac{1}{3}\)
\(x=\frac{1}{4}-\frac{2}{3}\)
\(x=-\frac{5}{12}\)
Vậy \(x=-\frac{5}{12}\)
(x - 2/3) x 3 = 3/4
x - 2/3 = 3/4 : 3
x - 2/3= 1/4
x = 1/4 + 2/3
x = 11/12
Vậy x = 11/12.